2011
DOI: 10.1524/ract.2011.1823
|View full text |Cite
|
Sign up to set email alerts
|

Highly stable acyclic bifunctional chelator for 64Cu PET imaging

Abstract: Ligand L 1 , based on a pyridine scaffold, functionalized by two bis(methane phosphonate)aminomethyl groups, was shown to display a very high affinity towards Cu(II) (log K CuL = 22.7) and selectivity over Ni(II), Co(II), Zn(II) and Ga(III) (Δ log K ML > 4) as shown by the values of the stability constants obtained from potentiometric measurements. Insights into the coordination mode of the ligand around Cu(II) cation were obtained by UV-Vis absorption and EPR spectroscopies as well as density functional theor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
20
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(22 citation statements)
references
References 85 publications
2
20
0
Order By: Relevance
“…12 The sequence of LM stability constants (Table 3) is indeed in agreement with the Irving-Williams series which defines that the classical thermodynamic order for transition-metal complexes is Mn(II) < Fe(II) < Co(II) < Ni(II) < Cu(II) > Zn(II). This binding selectivity also exists for other polyaminomethanephosphonate ligands such as DO2P.…”
Section: Resultssupporting
confidence: 75%
See 2 more Smart Citations
“…12 The sequence of LM stability constants (Table 3) is indeed in agreement with the Irving-Williams series which defines that the classical thermodynamic order for transition-metal complexes is Mn(II) < Fe(II) < Co(II) < Ni(II) < Cu(II) > Zn(II). This binding selectivity also exists for other polyaminomethanephosphonate ligands such as DO2P.…”
Section: Resultssupporting
confidence: 75%
“…The complexation should be efficient and rapid at room temperature and at low concentration, at a pH suitable for biological applications. 11,12 We have also shown that L 1 can be derivatized into an activated phosphonated bifunctional chelate L* (Scheme 1) which can be coupled to small peptides or large antibodies. [8][9][10][11][12][13][14][15][16] With phosphonated ligands, the thermodynamic stability constants of the Cu(II) complexes are notably higher than those of their acetate analogues.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…L 2 showed one band, centered at 263 nm, attributed to the π-π* transition of the pyridine rings, which underwent a hypochromic variation with the appearance of shoulders upon increase of the pH. 60 The statistical analysis of the potentiometric and spectrophotometric data versus pH was achieved with Hyperquad2008 85 and Hypspec softwares, 78 respectively, and led to the determination of five protonation constants of ligand L 2 in the pH range from -0.59 to 11.93 (Table 4). The first protonation constant (log K 1 H =11.5(3)) was assigned to the tertiary amine of the bispidine skeleton.…”
Section: Synthesis Of Ligand Lmentioning
confidence: 95%
“…[12] Within the frame of our search for highly efficient complexes for molecular imaging, we have been interested in the design of polyphosphonated chelates for luminescence, [7,13] or radiochemicala pplications. [14] In this study,w er eport on the coordination behavior of as eries of bis-,t ris-and tetraphosphonated ligands( Scheme 1) with lanthanide cations and we particularly inspect the influence of the number of phosphonic coordinating units on the relaxation properties of the corresponding Gd III chelates.…”
Section: Introductionmentioning
confidence: 99%